Influence of herbal medicine in periodontics - Vangara Aditya; Kharidhi Laxman Vandana (SRM Journal of Research in Dental Sciences)
The nonsurgical treatment for periodontitis includes scaling and root planning and the use of antimicrobial agents. Patients with periodontitis are now being treated with supplementary antimicrobials as a result of a growing understanding of the infectious nature of periodontal diseases. The use of herbs in the treatment of periodontitis is growing as an adjunct to nonsurgical modes of treatment, either in single herb or polyherbal therapy.